An In-Situ Thermogravimetric Study of Pyrolysis of Rice Hull with Alkali Catalyst of CaCO3 - Gan, D.; Chin, Bridgid; Loy, A.; Yusup, S.; Acda, M.; Unrean, P.; Rianawati, E.; Jawad, Z.; Lee, R. (2018)
© Published under licence by IOP Publishing Ltd. Pyrolysis of rice hull (RH) with the presence of CaCO3 catalyst was carried out in this study to understand the effect of alkali catalyst in the thermal degradation behaviour and evaluate the kinetic parameter of rice hull for bio-oil or syngas production. Five different heating rates of the pyrolysis experiments at 10, 20, 30, 50, and 100 Kmin-1 were carried out in thermogravimetric analysis (TGA) equipment. Model fitting kinetic Coats Redfern integral method was applied in this study to estimate the activation energy (EA) and pre-exponential (A) value of catalytic pyrolysis in RH. The results showed that the maximum degradation increased from 6.69 to 52.67 wt% min-1 as heating rates increases from 10 to 100 Kmin-1. Besides that, the EA of the catalytic pyrolysis for RH using CaCO3 catalyst 60.86 kJmol-1 which is lower than other similar pyrolysis reaction reported in literature i.e. 77.4 kJ/mol. Meanwhile, the A value for the catalytic pyrolysis for RH using CaCO3 catalyst was 4.68×1010 min-1 which is significantly higher than 1.1×106 min-1 as reported in literature for non-catalytic pyrolysis of rice husk.